Evaluation of OSPE in FCPS Part II (Obs/Gynae) Examination Conducted by Bangladesh College of Physicians and Surgeons (Bangladesh Journal of Medical Education, 2017)
Assessment plays a major role in the process of medical education. The clinical examination plays a key role in the assessment of students' competence to practice medicine. The conventional method of assessment does not include the assessment of clinical psychomotor skill, which students are learning throughout their clinical postings .The judgement of students performances is purely subjective and the same performance is graded differently by different examiners. A major advances in this area has been the formulation of an objective structured clinical/practical examination (OSCE/OSCE), which has been implemented successfully. The objectives of this study were to evaluate OSPE in FCPS part II exam in Obs and Gynae conducted by Bangladesh College of Physicians and Surgeons (BCPS) in terms of exploration of quality of assessment tools as well as the opinion of the students and the examiners regarding OSPE. A cross-sectional observational study was conducted among 150 students appearing in FCPS part II examination in Obs and Gynae of Bangladesh College of Physicians and Surgeons . Among the examiners 30 were included in the study. Study instrument consisted of two sets of self- administered questionnaires, one for the students and one for the examiners. Attitudes of students and examiners were collected by a grading scale (Likert scale). Different stations were analyzed by criteria of content coverage, skills assessed, clarity of languages, dominant domain assessed and time allocated for the task. By analyzing the results of three sessions it shows that the percentage of pass varies from ten to fourteen percent .The overall opinion regarding OSPE shows that 54 percent of the students strongly agreed that this assessment system is a comprehensive one. About thirty seven percent and forty percent of students agreed on that it can assess wide range of knowledge and clinical competencies respectively .However student felt that clinical competencies respectively .However student felt that it was a strong anxiety producing experience. And concerns were expressed regarding the ambiguity of some questions and inadequacy of time for expected tasks in some stations. The majority of the students felt they were well oriented about the exam and that the required tasks were consistent with the actual curriculum that they were taught. Ninety percent of examiners strongly agreed that it is a comprehensive system of assessment. Majority strongly agreed that it's a useful method of identifying gaps and weaknesses in competencies. About seventy percent agreed that checklists were well prepared. But forty percent had the opinion that there was some ambiguity of languages and ambiguity of instructions. OSPE quality evaluation showed coverage of content was adequate. Most of the domain assessed was psychomotor domain. In conclusion, both students and examiners agreed that the assessment was comprehensive and it was an objective and fair process. Overall opinions suggested that OSPE were restrictive, non discriminative and simplistic. The very nature of OSPE made it different from the traditional method. It was very much comprehensive and valid, covers a wide range of contents including practical skills.Bangladesh Journal of Medical Education Vol.4(1) 2013: 8-15